The low health literacy in Latin America and the Caribbean: a systematic review and meta-analysis - Patricia Romualdo de Jesus; Bianca Vendruscolo Bianchini; Patrícia Klarmann Ziegelmann; Tatiane da Silva Dal Pizzol (BMC, 2024)
Abstract Background Health literacy (HL) impacts people's health and well-being. In Latin America and the Caribbean (LAC), there are no general estimates of the prevalence of low HL. This study aimed to estimate the prevalence of low HL among citizens of LAC and identify the tools used to measure it. Methods We included observational studies quantifying the prevalence of low HL in people living in LAC. We searched PubMed, CINAHL, EMBASE, ERIC, LILACS, PsycINFO, Redalyc, SciELO, Web of Science, PQDT, and the reference lists of the included studies in June 2023. Two reviewers independently conducted the selection, extraction, and risk of bias assessment using the JBI Critical Appraisal Tools. Meta-analysis of proportions using random effects models was used to summarize the prevalence of low HL estimated. This prevalence was measured in each study using different classification methods: word recognition items, reading and numeracy comprehension items, and self-reported comprehension items. Results Eighty four studies involving 23,914 participants from 15 countries were included. We identified 23 tools to assess HL, and most of the studies were carried out in health services. The pooled prevalence of low HL were 44.02% (95%CI: 36.12-52.24) for reading and numeracy comprehension items, 50.62% (95%CI: 41.82-59.39) for word recognition items, and 41.73% (95%CI: 31.76-52.43) for self-reported comprehension items. Conclusion Despite the variability in the prevalence of low HL and a diversity of tools, the average of low HL is of concern. Almost half of the participants in the included studies have low HL. Most of the studies targeted users of healthcare services. Further research investigating the prevalence of low HL in the general population and actions focused on health education, communication, and information are necessary. Trial registration PROSPERO (CRD42021250286).